2008
DOI: 10.1111/j.1469-1795.2008.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population parameters in a threatened arctic fox population using molecular tracking and traditional field methods

Abstract: Comprehensive population parameter data are useful for assessing effective conservation actions. The Fennoscandian arctic fox Alopex lagopus is critically endangered and the population size is estimated at 120 individuals that are fragmented into four isolated populations. Here, we use molecular tracking and visual observations to estimate population size and survival in one of the populations on the Swedish mountain tundra during a year of low food availability. We collected 98 arctic fox faecal samples durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…The interpretation of the mark-loss probabilities and/or recapture efficiency rates will generally be of interest in any study where different marks can be applied to different animals. There are a number of studies of this kind, for example involving both tagging and DNA-based methods (Meijer et al 2008), and marking methodology may have animal welfare or conservation implications in some cases (McCarthy and Parris 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of the mark-loss probabilities and/or recapture efficiency rates will generally be of interest in any study where different marks can be applied to different animals. There are a number of studies of this kind, for example involving both tagging and DNA-based methods (Meijer et al 2008), and marking methodology may have animal welfare or conservation implications in some cases (McCarthy and Parris 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dalén, Götherström et al (2004) demonstrated how mitochondrial analysis of faecal samples can be used to distinguish between Arctic and red (Vulpes vulpes) foxes as well as wolverines (Gulo gulo), and subsequently Dalén, Elmhagen et al (2004) used this method to show that while red and Arctic foxes are sympatric in winter, Arctic foxes retreat to higher altitudes in summer, which most likely is due to the increased risk of red fox predation on Arctic fox cubs at lower altitudes. This method was later developed by Meijer et al (2008), who used microsatellite genotyping of faecal samples to estimate population size and survival in the southernmost Swedish subpopulation. In total, 98 Arctic fox faecal samples were genotyped at nine microsatellite loci.…”
Section: Genetic Monitoringmentioning
confidence: 99%
“…Molecular tracking can also be used to estimate other population parameters (Schwartz et al 2007). Meijer et al (2008) estimated the age-specific finite survival rate during one year (summer to summer) by combining molecular tracking with visual observations and matching the faecal genotypes to genotypes of known origin (collected as tissue samples during ear-tagging). Juveniles displayed a lower survival than the adults during autumn, whereas there was no evidence for age-specific survival difference during spring.…”
Section: Genetic Monitoringmentioning
confidence: 99%
“…The study was conducted on the sub-arctic tundra in Helagsfjällen (62.53 N 12.40 E), Jämtland county, Sweden (see Meijer et al 2008). Since 2001, approximately 75% of all born cubs have been ear-tagged (Dalton Rototags) with unique colour combination which allows individual identification.…”
Section: Study Areamentioning
confidence: 99%